Recognizing Consumer Behavior from the Perspective of Continuance Intention Theory: A proposed framework - Raphael Reano Pandrika Parikesit; Dudi Permana (Dinasti Publisher, 2023)
In recent decades, the level of internet usage, especially in Indonesia, has shown significant growth. This encourages the growth of the use of various applications, one of which is an online transportation application. GoRide service on the Gojek application is one of the applications that is often used. This study will examine the influence of perceived usefulness, satisfaction, attitude variables on the continuance intention of GoRide users on the Gojek application. The population of this study is all Gojek application users in the last three months in the Jabodetabek area with the sampling technique used is non-probability sampling with a minimum sample number of 170 respondents. Furthermore, this research will use SEM PLS 4 in the data analysis process. The results of this research are in the form of a proposed framework that will be continued as empirical research.